Composition and thickness of gold and silver nose decorations from the tomb of the Lady of Cao determined by combining EDXRF-analysis and X-ray transmission measurements - Cesáreo, R. (2014)
Thirty four nose decorations from the tomb of the Lady of Cao has been analyzed by EDXRF-analysis and transmission measurements. These nose decorations are made partially on gold, and partially on silver. EDXRF-analysis showed that, while gold areas all show a similar composition, silver areas exhibit an erratic composition, and also an unusual high percentage of gold, up to 35 %. To verify that this erratic composition is not depending on surface enrichment processes, X-ray transmission measurements were carried out, which gives the bulk composition of the samples. These last measurements completely confirm EDXRF-results. Therefore the conclusion could be that a high quantity of gold was added intentionally to the silver alloys, for not clear reasons, may be to avoid the oxidation process typical of high concentration silver in silver alloys.